Valero energy corporation case study - RETHA J. MATTERN; ZHI YANG BRIAN CHAN; JAMES ONDRACEK; ANDY BERTSCH; M. SAEED (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The purpose of this research is to delve into the business practices of Valero Energy Corporation. The Valero Energy Corporation (Valero) was founded in 1980 and has since grown to become a major petroleum refiner in the U.S. and international oil and gas industries. Valero is a Texas-based oil and ethanol company that operates 15 refineries and 14 plants.Method: The methods used by Valero Energy Corporation were dissected using a case study approach.Findings: The findings of this study show that Valero Energy Corporation is up against difficulties in the industry’s midstream and downstream, with an emphasis on external factors like weather and geopolitical influences. Valero Energy Corporation will continue to face challenges soon, even though crude oil prices appear to stabilize. This is because of the continued volatility in the market and the slowdown in international economic growth. As a long-term strategy to prepare themselves for future economic uncertainty and unsteady industry conditions, oil and gas companies will continue to enforce capital discipline. Though Valero’s strategic acquisitions and divestitures helped the company weather previous economic storms, the question remains whether or not the company’s current asset mix is optimal.Implications/Novel Contribution: Students at both the undergraduate and graduate levels of business study can benefit from the Valero Energy Corporation Case Study by applying concepts like critical thinking, qualitative and quantitative analysis, and decision-making. Valero Energy Corporation’s (Valero) efforts to remain competitive and generate above-average returns are the focus of this case study.